An Analysis of the Effects of Anthropogenic Factors on Vegetation Cover Change in Guanzhong, China - Bai, Ziyi; Dong, Zhibao; Xue, Liang; Cui, Yingying; Shi, Weikang; Chen, Guoxiang; Chi, Zheng; Zhang, Chong (Frontiers in Earth Science, 2022)
Exploring the impacts of anthropogenic factors on vegetation cover and future spatiotemporal trends in vegetation cover change are of great practical significance for sustainable management of the ecological environment. This study used the residual, trend analysis, Hurst index, and geographic detector methods to explore the spatiotemporal trends in the effects of anthropogenic factors on vegetation cover in Guanzhong, China from 2001 to 2018. The contributions of different kinds of anthropogenic factors to vegetation cover were quantitatively decomposed to identify those with the most effect. The main conclusions of the study included: 1) Although there was a positive trend in the effects of anthropogenic factors on vegetation cover from 2001 to 2018, this trend was projected to become negative in the future. This transition was evident in 45.53% of the total study area, mainly distributed in the cities of Baoji, Weinan, and Xianyang. The effects of artificial factors on reversing this deteriorating trend in the region should be noted. 2) The factors with the greatest influences on vegetation cover changes were popular tourist attractions, transportation, and urbanization rates. The influences of various factors on vegetation cover showed temporal variation, driven by societal and economic development, indicating the complexity and diversity of the influences of anthropogenic factors on vegetation cover. 3) Sustainable development should be promoted and the pressure on the ecology resulting from popular tourist attractions, the transportation network, and rapid urbanization should be reduced.